Indonesia : The Imperative for Reform - World Bank (Washington, DC, 2013)
In the one hundred days since assuming office, the new administration of Megawati Soekarnoputri has made little progress on structural and governance reforms. The events of September 11 and the slowdown in the global economy worsened the investment climate in Indonesia, adding to the government's already formidable array of challenges. Indonesia's recovery has lagged behind its neighbors and over half its population vulnerable to poverty, more than any other crisis country. Moreover, its fragile banking and corporate sectors, and the precarious state of its government finances, make the country highly vulnerable to risks--with immediate implications for fiscal sustainability. Donors need to be realistic about what is feasible, given strong vested interests, severe institutional weaknesses, the uncertainties arising from decentralization, and a turbulent transition to democracy. Progress is most needed in the key areas of structural reforms, good governance, and empowering and investing in the poor. Together with fiscal sustainability, they are consistent with the premise that stability, growth, and effective government are the key ingredients for long-lasting and sustainable poverty reduction.